683 TWO IS BETTER THAN ONE!. (15th December 2022) - Circhetta, Simone; Ricottini, Elisabetta; Nusca, Annunziata; Melfi, Rosetta; Mangiacapra, Fabio; Gallo, Paolo; Cocco, Nino; Rinaldi, Raffaele; Cammalleri, Valeria; Bernardini, Federico; Nobile, Edoardo; Filippis, Aurelio De; et al.
Abstract: Patients suffering from atrial fibrillation (AF) and severe aortic stenosis thus undergoing transcatheter aortic valve implantation (TAVI) have a worse prognosis than those in sinus rhythm. One of the reasons of this is related to the augmented bleeding risk associated with oral anticoagulation (OAC). Left atrial appendage occlusion (LAAO) represents a therapeutic choice to avoid this drug intake and to reduce this kind of adverse outcome. So, a combined procedure of TAVI and LAAO could be an option for TAVI candidates with AF to omit the need for OAC. The clinical case concerns an 85-year-old man with hypertension and dyslipidemia with a history of recent syncope and permanent atrial fibrillation in therapy with antithrombotic drug. Brain MRI performed during hospitalization showed numerous hemosiderin deposits with microhemorrhagic foci thus contraindicating oral anticoagulation. Severe aortic stenosis has also been found to the transthoracic echocardiogram with a mean gradient of 35 mmHg and confirmed by transesophageal echocardiogram with a planimetric area of 0.8 sq.cm. Furthermore, given the finding of significative left circumflex artery disease, after Heart Team discussion and the execution of CT scan that demonstrated the feasibility of transcatheter approach, it was decided to perform in a single session percutaneous coronary intervention (PCI) plus TAVI plus left atrial appendage closure (LAAO). This kind of approach allowed a quick recovery to the patient after a short period of hospitalization. After six months from interventional procedure his NYHA (New York Heart Association Functional Classification) status improved abutting on I/II class. As described above, it can be deduced that combined approach (TAVI+LAAO) is feasible for certain kind of patients thus avoiding surgical approach and long hospitalization. Furthermore, multimodality imaging is of critical importance to plan a complex procedure and an accurate step-by-step pre-procedural strategical planning is the key for procedural success.